KNOWLEDGE, ATTITUDES AND BEHAVIOR OF STUDENTS OF THE MEDICAL COLLEGE OF APPLIED SCIENCES IN BELGRADE RELATED TO THE SIGNIFICANCE OF HPV INFECTION, THE HPV VACCINE AND OTHER PREVENTIVE MEASURES - Dabic, Marijana (HEALTH CARE, 2022)
Introduction/Aim: Knowledge and awareness of the importance of the HPV vaccine against human papillomavirus (HPV) can greatly contribute to the reduction of cervical cancer and other malignant tumors. The aim of this study is to assess the knowledge, attitudes and behavior of students about HPV infection, as well as to propose measures for the better coverage of young people with the HPV vaccine.Methods: A cross-sectional study included 449 students of healthcare of the Medical College of Applied Sciences in Belgrade in the period from March to May, 2019. Data were collected using a questionnaire. Chi-square test and Fisher’s exact tests were used for the statistical analysis of data.Results: The average age of students was 21.02±2.59 years. 86.0% of students assessed their knowledge about the HPV vaccine as satisfactory. Teachers had the greatest influence on their knowledge about the HPV vaccine (79.7%), followed by the electronic media (10.7%). Medical platforms for information about the HPV vaccine were used by only 9% of students. Students acquired the first information and a certain degree of knowledge about HPV infection and the HPV vaccine in high school (80.4% and 65.6%). Only 3.4% of students think that young people in Serbia are sufficiently informed about HPV infection and 0.4% about the HPV vaccine. Every second student believes that peer education in schools is one of the ways to better inform young people. About 94% of students know that there is an organized screening for cervical cancer in our country. Only 10.2% of students wanted to vaccinate their child with the HPV vaccine, and those who would not do so cite the insufficient information about the safety and effectiveness of the vaccine as their main argument (81.6%). Respondents who were for the HPV vaccine significantly less frequently underwent regular gynecological examinations.Conclusion: Students of the Medical College of Applied Sciences in Belgrade believe that there should be better education about HPV infection and the vaccine, which could be best realized by conducting peer education.
Keywords: HPV vaccine, students, knowledge, attitudes